Diplomacy, family ties and divided loyalties: Joan of Navarre as a queenly diplomat - Woodacre, Elena (En la España Medieval, 2025)
This article examines the diplomatic agency of Joan of Navarre (c. 1369-1437) as queen consort and queen dowager of England. It focuses particularly on the period between 1403 and 1419 and her role as a key pivot point between England and Brittany, as the wife and stepmother of English kings and the mother of Jean V of Brittany. The case study demonstrates key strategies that Joan used to engage in diplomatic relations, both formal aspects such as gift giving and informal “back-channel” methods of influence using her familial networks and trusted courtiers. It offers a reconsideration of the important role that Joan, like other queens and royal women, played in diplomacy which has often been overlooked as the focus has been on male actors and formal negotiations.